CAR-based cell therapy for autoimmune diseases - Li, Xiu; He, Chao; Wang, Ke; Xu, Guo-Ying; Xie, Ya-Chao; Ying, Xin-Yu (Frontiers in Immunology, 2025)
Chimeric antigen receptor (CAR)-based cell therapies, initially designed for oncology, are rapidly advancing as a novel and highly targeted approach for the treatment of autoimmune diseases (AIDs). By harnessing engineered immune cells to eliminate autoreactive immune components or restore immune homeostasis, CAR-based strategies offer new avenues beyond conventional immunosuppression. In this review, we summarize current applications of CAR-T cells in autoimmune diseases, and discuss emerging approaches including CAR-Tregs, chimeric autoantibody receptor T (CAAR-T) cells, CAR-NK cells, and CAR-macrophages. We also describe advances in CAR design, including antigen selection, co-stimulatory domains, and safety control mechanisms, which are critical for improving therapeutic precision and reducing side effects. In addition, we highlight the role of synthetic biology in enabling more flexible and controllable CAR functions. Finally, we discuss the main challenges facing clinical translation, such as antigen specificity, long-term persistence, and manufacturing feasibility. These developments collectively support the potential of CAR-based therapies as a next-generation option for autoimmune disease treatment.